Developing the Educaplay grammar assessment for tenth graders of senior high school in Kediri - Ningrum, Dyah Ayu Kusuma; Ningrum, Ary Setya Budhi; Indah, Rohmani Nur; Syaifulloh, Burhanudin (Universitas Negeri Yogyakarta, 2025)
Teaching English as a Foreign Language (EFL) faces challenges in engaging students with grammar instruction. Grammar is a critical component of language education that underpins effective communication and comprehension. This study aims to develop an Educaplay-based grammar assessment tool for tenth-grade students at Senior High School 5 Taruna Brawijaya in Kediri, Indonesia. The instruments used for data collection included a grammar test, validated by experts to ensure content validity, and a questionnaire for expert feedback. The Research and Development (R&D) method was employed, following the steps outlined by Borg and Gall (1983), which involve product development, validation, and iterative revisions. Data analysis involved assessing the validity, reliability, difficulty index, and item discrimination of the grammar test. The findings indicate that the tool is valid and reliable, with a Cronbach's Alpha of 0.884, although there is a need for more challenging items to better cater to a range of student abilities. It is concluded that Educaplay provides an effective and engaging alternative to traditional grammar assessments. These results are expected to provide valuable insights into how digital platforms such as Educaplay can be used to improve grammar teaching and student learning outcomes, not only in Indonesia but also in other countries facing similar challenges. The study recommends further development of the tool to incorporate more complex items and suggests exploring the long-term effects of using digital tools like Educaplay in grammar education.